Wczesnokapitalistyczne metropolie - Manchester = Early capitalist metropolises - Manchester - Pater, Łukasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author of this article describes the metropolitan status of Manchester. Firstly, the broader context of hanges observed in Europe since the 16th century is described. England and its cities played the leading role in those processes. This is where the changes first took place and then spread to the rest of Europe. Subsequently, the description of changes occurring in Manchester since the 18th century is made with special emphasis on economic changes and their consequences for the position of the city in international city hierarchy. There are also reasons pointed out for the dynamic expansion of Manchester in this period.
Keywords: Manchester; miasta - Anglia; miasta; historia; metropolia